Antibacterial Character of Cationic Polymers Attached to Carbon-Based Nanomaterials - Plachá, Daniela; Muñoz-Bonilla, Alexandra; Škrlová, Kateřina; Echeverria, Coro; Chiloeches, Alberto; Petr, Martin; Lafdi, Khalid; Fernández-García, Marta (Nanomaterials (Basel, Switzerland), 2020)
The preparation of hybrid polymeric systems based on carbon derivatives with a cationic polymer is described. The polymer used is a copolymer of a quaternizable methacrylic monomer with another dopamine-based monomer capable of anchoring to carbon compounds. Graphene oxide and graphene as well as hybrid polymeric systems were widely characterized by infrared, Raman and photoemission X-ray spectroscopies, electron scanning microscopy, zeta potential and thermal degradation. These allowed confirming the attachment of copolymer onto carbonaceous materials. Besides, the antimicrobial activity of hybrid polymeric systems was tested against Gram positive Staphylococcus aureus and Staphylococcus epidermidis and Gram negative Escherichia coli and Pseudomonas aeruginosa bacteria. The results showed the antibacterial character of these hybrid systems.
Keywords: cationic group; graphene; antimicrobial; polymer; dopamine; graphene oxide; functionalizations